Pengaruh Konsentrasi Pemanis Alami (Stevia) Pada Minuman Kesehatan Tradisional Terhadap Tingkat Kesukaan Konsumen (Organoleptik): Effect of Natural Sweetener Concentration (Stevia) in Traditional Health Drinks on Consumer's Level of Taste (Organoleptic) - Muhammad Abu Bakar; Anis Nurhayati; Imron Rosidi (Journal of Agriculture and Social Development, 2023)
Traditional drink is one of the herbal drinks with various kinds of benefits for the body and is one of the results of local wisdom which has been maintained for a long time by the people of Indonesia. As is the case with the Kebonagung drink, a traditional drink originating from the Regency/City of Pasuruan, East Java. The main ingredient for making Kebonagung drink is cane sugar. Stevia Rebaudiana Bertoni is an herbal plant belonging to the Asteraceae family, which is used as a non-caloric natural sweetener. The leaves contain stevioside and rebaudioside. Both have blood pressure-lowering and antipyperlicemic potential. Stevia is a natural sweetener alternative. However, in Indonesia, the stevia plant has not shown an important role as a sweetener source. The purpose of this study was to determine the effect of adding liquid stevia to traditional drinks on consumer preferences. This research method used a Completely Randomized Design (CRD) with 5% & 1% BNJ Follow-up Test which consisted of 4 treatments namely F1 (0.5%), F2 (1.0%), F3 (1.5%), F4 (2.0%). The results of the research from organoleptic (sensory) test data showed that samples treated with F3 (1.5% stevia concentration) had the most favorable level of preference for aroma (3.63), color (2.17), taste (2.08) ) and aftertaste (2,13).